Functional Outcome of Isolated Middle to Distal Third Ulnar Shaft Fracture in Adults with Square Nail Fixation - KC, Dipendra; Shrestha, Dinesh Kumar; Karki, Prateek; Shrestha, Sabin; Yogi, Sushil (Journal of Nepalgunj Medical College, 2022)
Introduction: Isolated ulnar shaft are uncommon injuries with most of the fractures occurring following direct trauma.  Open reduction and internal fixation with plating is the gold standard treatment but is associated with complications. Treatment with square nail provides rotational stability, is cheaper, safer with minimum complications of plating.Aims: To evaluate the functional outcome of isolated fracture of middle third to distal third ulna treated with square nail.Methods: This prospective observational study was conducted in the Department of Orthopedics at Nepalgunj Medical College Teaching Hospital Kohalpur from September 2018 to August 2022. Patients aged above 18 and below 60 years who had displaced isolated fracture of middle third or distal third of ulna were evaluated for demographic details, union, functional outcome and associated complications. All of the fractures of ulna were treated by square nail and outcomes were evaluated using disability of arm, shoulder and hand (DASH) score and Grace and Eversmann scoring system.Results: In this study of 39 patients with the mean age of 30.84±8.12 years, 56.4% of the patients were in age group 18-30 years, 27 (69.2%) were males and 12 (30.8%) were females.  The right limb was fractured in majority, distal third was more commonly involved, physical assault was the most common mode of injury, transverse was the most common fracture pattern. The average time to union was 11.61±2.74 weeks. Most (74.4%) of the patients had good result in DASH score and most (94.9%) had good to excellent result in Grace and Eversmannscoring at final follow-up. The most common complication noted was olecranon bursitis (17.94%) followed by skin irritation (12.82%).Conclusion: Square nail fixation of isolated middle third to distal third ulna is safe procedure with few complications, produces excellent to good results.